Prevalence of infectious diseases in Sonali chickens at Bogra Sadar Upazila, Bogra, Bangladesh - Talukdar, Md. Lipon; Zuhra, Fatema Tuz; Islam, K. M. Ehasanul; Ahmed, Md. Selim (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: The study was conducted to determine the prevalence of infectious diseases in Sonali chickens at Bogra Sadar Upazila, Bogra, Bangladesh. Materials and methods: A total of 258 sick and dead Sonali chickens were examined for the diagnosis of different infectious diseases based on history, clinical findings and postmortem lesions of dead and sacrificed birds. Results: Infectious Bursal disease (IBD) was recorded in 14.72% (n=38/258) cases. Similarly, Newcastle disease (ND), Coccidiosis, Colibacillosis and Mycoplasmosis were recorded in 11.24% (n=29/258), 13.95% (n=36/258), 14.72% (n=38/258), 12.79% (n=33/258) cases, respectively. Mixed infection of IBD, ND and Coccidiosis found in 16.67% (n=43/258) birds. On the other hand, mixed infection of IBD, ND and colibacillosis was recorded in 15.89% (n=41/258) cases. Conclusion: It is concluded that several infectious diseases are commonly present in Sonali chicken in the study area of Bangladesh. Mixed infections are more prevalent as compared to single infection. Proper hygienic management and appropriate vaccination should be taken in consideration for effective control the diseases. Further microbiological and molecular diagnoses are suggested for detail studies of these diseases and their pathogens. http://doi.org/10.5455/javar.2017.d188